IMPLEMENTASI METODE SMALL GROUP DISCUSSION UNTUK MENINGKATKAN AKTIVITAS BELAJAR FIKIH PESERTA DIDIK KELAS X MA TANBIHUL GHOFILIN BAWANG BANJARNEGARA TAHUN 2021/2022 - Cinanthya Yuwono; Naufal , Naufal (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2022)
The aims of this study is: 1) Knowing the use of the Small Group Discussion method in fiqh learning for class X MA tanbihul Ghofilin Bawang students; 2) Knowing the difference between learning activities using the Small Group discussion method and those who do not use the small group discussion method in class X MA Tanbihul Ghofilin students; 3) Knowing the increase in learning activities using the small group discussion method for class X MA Tanbihul Ghofilin Bawang students.The research according to experimental methods using non-equivalent control group design. The subjects in this study were students of class X Agama 3 and X Agama 4 MA Tanbihul Ghofilin which totaled 60 students who were divided into two groups, namely class X Agama 3 as the Experimental class and Class X Religious 4 as the control class. Learning begins with providing pretest questions to find out the extent of student learning activities. Experimental students were given learning using the small group discussion method while the control group used conventional learning methods. The experimental group and the control group were given the final test in the form of posttest questions in writing. Then the results were processed, analyzed, and compared using a t-test and a scor gain test to determine the differences and activities between the two groups to be studied.The results showed that there were differences in learning activities between the experimental class and the control class with evidenced by the t-test and the control class with evidenced by the t-test calculation showing tcount of count 2,0001 > ttable 10.6 with a significance level 0f 5 % and degress of freedom 58. It was proveb by the calculation of N-gain of 0,76 with category.